Expectations concordance and stock market volatility: Knightian uncertainty in the year of the pandemic - Roman Frydman; Nicholas Mangee (Journal of Risk and Financial Management, 2021)
This study introduces a novel index based on expectations concordance for explaining stock-price volatility when novel events that are each somewhat unique cause unforeseeable change and Knightian uncertainty in the process driving outcomes. Expectations concordance measures the degree to which KU events are associated with directionally similar expectations of future returns. Narrative analytics of daily news reports allow for the assessment of bullish versus bearish views in the stock market. Increases in expectations concordance across all KU events results in reinforcing effects and an increase in stock market volatility. Lower expectations concordance produces a stabilizing effect wherein the offsetting views reduce market volatility. The empirical findings hold for ex post and ex ante measures of volatility and for OLS and GARCH estimates.
Keywords: D81; D84; G12; G14; 330; expectations concordance; narrative analytics; volatility; Knightian uncertainty